Adverse events of neoadjuvant combination immunotherapy for resectable cancer patients: a systematic review and meta-analysis - Feng, Yuqian; Guo, Kaibo; Jin, Huimin; Jiang, Jing; Wang, Menglei; Lin, Shengyou (Frontiers in Immunology, 2024)
Background: Neoadjuvant combination immunotherapy is changing the treatment landscape for patients with cancer. Exploring the incidence of immune-related adverse events (irAEs) in relation to this novel approach may provide valuable insights for future clinical investigations.Methods: This review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. PubMed, Embase, Cochrane Library, American Society of Clinical Oncology (ASCO), and European Society of Medical Oncology (ESMO) websites were searched for all relevant literature from their inception to November 24, 2023. We then extracted the required data from the included studies and used the R software to analyze the pooled incidence of irAEs. Subgroup analyses examined the pooled incidence of irAEs according to cancer and combination types using a random-effects model.Results: Sixteen studies involving 501 patients were included in the meta-analysis. Considering the heterogeneity of the study design, we analyzed the randomized controlled studies (RCTs) and the single-arm studies separately. In RCTs, the incidence of any-grade irAEs was 95.0% (95% confidence interval [CI] 87.3-99.3) and that of grade ≥3 irAEs was 24.0% (95% CI 13.7-36.0). In single-arm studies, the incidence of any-grade irAEs was 89.4% (95% CI 75.0-98.0) and grade ≥3 irAEs was 20.3% (95% CI 8.7-35.2). In both RCTs and single arms, the most common any-grade irAEs were rash and fatigue, while the most common grade ≥3 irAEs was abnormal liver function and colitis. Due to irAEs, 9.4% of patients in RCTs and 6.9% of patients in single-arm studies did not complete the prescribed neoadjuvant treatment cycle.Conclusion: This study comprehensively summarized the incidence of irAEs in neoadjuvant combination immunotherapy. The occurrence of irAEs varies depending on the cancer and combination types. Our meta-analysis provides clinicians with essential guidance for the management of patients with cancer.